2013
DOI: 10.1590/s0004-27302013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Associations among physical activity, comorbidities, depressive symptoms and health-related quality of life in type 2 diabetes

Abstract: Objective: To investigate associations between physical activity, comorbidity severity, depressive symptoms, and health-related quality of life in type 2 diabetes mellitus. Subjects and methods: All individuals, 200 patients and 50 controls, aged from 40 to 60 years, were investigated by interview, and all variables were measured concurrently. Physical activity was evaluated by the International Physical Activity Questionnaire (IPAQ), Health-Related Quality of Life (HRQL) by the Short-Form Health Survey (SF-36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
38
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 38 publications
8
38
1
7
Order By: Relevance
“…In the present study, 11.9% of the patients with DM2 were inactive, 50% were active and 17.9%, very active. is nding is not in accordance with that of another study conducted in the city of Fortaleza, Brazil, in which 40% of the sample was inactive, 20% active and 8% very active 15 . On analyzing distribution by gender according to the IPAQ classi cation, most participants with DM2 were active or very active; speci cally, 57.4% of the men and 60% of the women.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…In the present study, 11.9% of the patients with DM2 were inactive, 50% were active and 17.9%, very active. is nding is not in accordance with that of another study conducted in the city of Fortaleza, Brazil, in which 40% of the sample was inactive, 20% active and 8% very active 15 . On analyzing distribution by gender according to the IPAQ classi cation, most participants with DM2 were active or very active; speci cally, 57.4% of the men and 60% of the women.…”
Section: Resultscontrasting
confidence: 97%
“…ese ndings corroborate those of other studies that showed that age was inversely correlated with level of physical activity [13][14][15][16] In this study, the men classified as inactive according to the IPAQ presented poor glycemic control. Of the participants with good glycemic control, regardless of BMI, 68.9% were classi ed as active or very active.…”
Section: Ipaqsupporting
confidence: 91%
“…iabetes mellitus (DM), giderek artan sıklığı ve yüksek mortalitesi ile günümüzün en ciddi sağlık sorunlarından birisini oluştur-maktadır. [1][2][3][4][5][6] 2010 yılı itibarıyla yaş aralığı 20-79 yıl olan erişkin bireylerde dünya diyabet prevalansı %6,4 ile 285 milyon iken, bu oranın 2030 yılında %7,7'lik artış ile 439 milyon yetişkini etkileyeceği tahmin edilmektedir. Bu oran gelişmekte olan ül-kelerde %69 iken gelişmiş ülkelerde %20'dir.…”
unclassified
“…with a great interest (1). They concluded that functional capacity is independently related to physical activity in diabetic patients, and that increasing patient independence and treating depressive symptoms can promote physical activity.…”
mentioning
confidence: 99%
“…Internationally recognized training programs and physical activity assessment scales should be validated before being accepted in each society; especially in T2DM. Before implementation of these programs and scales, community-based assessment is required for suitability, both in this study and in others (1)(2)(3).…”
mentioning
confidence: 99%